Pengaruh Penerapan Code of Conduct dan Sistem Role and Play Terhadap Kinerja Karyawan - Kaban, Jop Kristian; Safrin, Feby Aulia; Siregar, Onan Marakali (Peneliti.net, 2025)
n realizing good employee performance, commitment from all elements of the company is needed. This commitment can be arranged in the form of a code of ethics for employees in carrying out their duties. In addition, managing employee morale is important in realizing good performance, boredom is a problem for employees because they always face the same tasks. This can be done by job rotation to refresh employees, but this is often opposed because it is considered to hamper employee career stability. This research was conducted at PT Bank Tabungan Negara KC Medan. The reason for choosing this place is in the financial statements of 4 government-owned banks (BRI, Mandiri, BNI, BTN) PT Bank Tabungan Negara has the highest level of NPL (Non-Performing Loan) or bad credit. The reason is that the company began to focus on the consumer credit segment so that the handling of bad debts decreased slightly. This research uses a quantitative method with an associative approach. The sampling technique was random sampling and involved 46 respondents. Primary data was obtained directly by distributing questionnaires through form while secondary data was obtained through literature studies. The data analysis methods used are the validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that the code of ethics variable (X1) has a significant effect on employee performance, and the role and play system variable (X2) also has a significant impact on employee performance. Likewise, variables X1 and X2 together (simultaneously) affect employee performance (Y). The coefficient of determination test shows that there is a fairly close relationship between the code of ethics and role and play on employee performance with a value of 84% which means the relationship is very near. In addition, the adjusted R-value is obtained which shows a contribution of 69%.